It equals 53X- a number is squared when it is multiplied by itself, so 7X by 7X = 49X. 2X by 2X =4X, so 49X + 4X is 53X.
2x2 + 7x - 15 = (2x - 3)(x + 5)
(x + 1)(2x + 5)
7x2 -4x -5x2 +2x = 2x2 -2x
You would factor 2x2 + 7x + 6 into (2x + 3) (x+2)
It is 9x
(x + 5)(2x - 3)
Since 7x + 13x +2x + 8 is an expression (there is no equal sign), there is no answer as to what x equals. However, this expression can be simplified to 22x + 8.
2x+3 = 9x 3 = 9x-2x = 7x 7x = 3 x = 3/7
(x - 2)(2x - 3)
It is an equation and the value of x is 1
2x+7x-10=4x+3-2x 9x-10=2x+3 7x=13 x=13/7ans
7x + 6 - 4x = 5 + 2x + 7 subtract 6 from both sides and combine the 5 and 7 on the right: 7x - 4x = 2x + 6 subtract 2x from both sides and combine the 7x and -4x on the left: x = 6
7x-4x+2x+5=2x+14 5x+5=2x+14 3x=9 x=3
-2x + 8 = 7x - 10 is technically an equation, in and of itself.
2x2 + 7x + 6 = 2x2 + 4x + 3x + 6 = 2x(x + 2) + 3(x + 2) = (x + 2)(2x + 3)
The value of x is 1
X = -3
(2x + 5)(7x - 3)
2x + ? = 9x9x - 2x = 7xso...2x + 7x = 9x